Estudos de adsorção de gases ácidos em faujasitas: experimentos e simulação molecular - Coelho, Juliana Amorim (2012)
Natural gas and biogas have in their composition methane, carbon dioxide, nitrogen, hydrogen, sulfur compounds (including hydrogen sulfide), etc. The carbon dioxide (CO2) and hydrogen sulfide (H2S) are highly undesirable. CO2 decreases the combustion power of the natural gas and H2S is an extremely toxic gas. Moreover, in the presence of moisture, they generate acids that corrode pipes and equipment. The absorption in amines solution is the conventional process to removal these gases. However, this process spends a lot of energy with the regeneration of the amines, besides forming corrosive by-products due to degradation of these. Thus, the physical adsorption using zeolites is a promising alternative for remove these gases. The aim of this study is to evaluate the adsorption of acid gases, CO2 and H2S, in pure, NaY and NaX, and modified, AgX, CaX and USY (dealuminated zeolite), faujasites through experimental methods and molecular simulation. The AgX and CaX zeolites were obtained by modifying the NaX zeolite. All absorbents were obtained and characterized. Experimental adsorption isotherms were obtained of CO2 on all studied adsorbents at 25 °C. The force field parameters were obtained by fitting to our own experimental data, CO2 in faujasites, and validated with available data taken from the literature, H2S in faujasites, by simulated isotherms using the Grand Canonical Monte Carlo (GCMC) method.